Framing Analysis of Reporting on Electric Transportation Subsidies in Indonesia during 2023 by Tirto ID - Harliantara Harliantara; Daniel Susilo (CV. Publikasi Indonesia, 2023)
The purpose of this study is to determine the Framing Analysis of Reporting on Electric Transportation Subsidies in Indonesia during 2023 by Tirto ID. EV becoming more discussed in today’s digital age, and some online in-depth news outlet is picking this discourse as part of participating in voicing the accurate news, which includes Tirto ID. With framing analysis, we can see how good, phrased news is still lacking in geographic source value despite the good narration in contributing to their media opinion. The topic itself is still warm material to be discussed for their upcoming policy. Electric transportation policies vary significantly between different countries as governments strive to reduce carbon emissions, promote energy efficiency, and transition to more sustainable modes of transportation. These policies encompass a range of measures, including incentives for electric vehicle (EV) adoption, infrastructure development, emissions regulations, and research funding.